SURFACE FINISH STUDY OF GREY CAST IRON CASTING SAMPLES FROM CONVENTIONAL & NON CONVENTIONAL MACHINING PROCESSES. - Abdullah Sani, Meor Hamzah (Universiti Teknologi Petronas, 2004)
The grey cast iron is considered to be unique in the great class of cast irons particularly, and irons and metals generally. In term of machining processes, the use of different machines would, from expectations from previous experiments, yield different value for the surface roughness. Although numerous studies had been done in the field of surface roughness, the use of a standard material, the grey cast iron, to compare the surface roughness produced by different machines, conventional and non-conventional would prove to be interesting. From the study done, it had been noted that different surface finish is attainable through different machining processes. Some machining processes could in fact, yield a wide range of surface roughness, simply by varying the parameters. On the other hand, some machining processes are only capable of delivering a smaller range of surface finish. From these data, the relevant machining processes with respect to the surface finish could be chosen. However, since the range of machining parameters is so wide and vast, further studies with respect to other machining parameters to obtain other ranges of surface finishes should be considered.